Validity of Wetland-Based Chemistry Media with Virtual Workspace-SCCRT Model to Improve 6c'skills in Society 5.0 - Rusmansyah Rusmansyah; Syahmani Syahmani; Yogo Dwi Prasetyo; Mohamad Nor Aufa; Arnita Purnama; Maulida Maulida; Kelly Sinaga; Maya Istyadji (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2025)
This study aims to develop and evaluate the validity of wetland-based chemistry learning media with the SCCrT model supported by Virtual Workspace to improve 6C skills in the Society 5.0 era. The method used is Research and Development (R&D) with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model, including validation by material and media experts. The results of validation by five experts showed that the learning media had very high validity (average score of 90%), especially in the aspects of curriculum suitability (92%) and relevance to environmental issues (91%). This media successfully integrates the concept of chemistry with sustainability issues and supports the development of 21st-century skills, such as critical thinking, collaboration, and civic thinking. These results show that the learning media developed is effective and relevant to improving the quality of chemistry learning and students' environmental awareness